Association of Helicobacter pylori with HLA-DR antigen expression in gastritis. Issue 1 (January 1992) - Wee, A; Teh, M; Kang, J Y
Abstract : AIMS: To assess the association between Helicobacter pylori-associated gastritis and HLA-DR antigen (class II antigen) expression. METHODS: Fifty endoscopic gastric biopsy specimens were studied for the presence of H pylori, degree and type of inflammation, and for HLA-DR antigen expression in the epithelium. The cases were chosen to represent different categories: inflamed gastric mucosa with (n = 13) and without (n = 20) H pylori, and non-inflamed mucosa (n = 17). RESULTS: The antigen was aberrantly expressed in the antral mucosal epithelium in 11 of 12 cases (92%) with acute-on-chronic gastritis when H pylori was also present. It was present in the antrum in only seven of 18 H pylori negative cases (39%) with acute-on-chronic/chronic gastritis. One of three cases of acute gastritis and three of seven cases of chronic gastric erosions (non-inflamed category) showed positive staining. Generally, there was more staining in the antral than body mucosa and in the surface/foveolar epithelium than in the glands. No aberrant HLA-DR antigen expression was found in the 10 cases of normal gastric mucosa examined. CONCLUSIONS: These findings suggest that H pylori may have a role in the induction of class II HLA antigen expression in chronic gastritis and lend support to the view that these organisms may be responsible for part of the inflammatory response.